Formulation and evaluation of lacosamide fast dissolving tablets - Srikanth Choudary Pallothu; Nellutla Sandeepthi (International Journal of Pharmacy and Analytical Research, 2022)
In spite of the fact that, the Oral administration of drug is the most popular route about 50-60% of total dosage forms are administered due to ease of ingestion, pain avoidance, versatility (to accommodate various types of drug candidates), and most importantly patient compliance. Solid oral delivery systems do not require sterile conditions and are therefore less expensive to manufacture. However the main aim of this study is to formulate Oral Disintegrating Tablets of Lacosamide to achieve rapid dissolution, absorption and further improving the bioavailability of the drug. Oral disintegrating Tablets and Films of Lacosamide were designed with a view to enhance the patient compliance and provide a quick onset of action.